DIAGNOSTIC IMAGING TURN AROUND TIME IN RADIOLOGY: LEAN MANAGEMENT - Jani, Kinjal; Patel, K. K.; Chaudhary, Bhupinder; Patel, Kesha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
BACKGROUND: Turnaround Time can help analyze workflows in patient care. It allows us to identify waste in diagnostic services. A well-timed diagnosis result can indeed impact the patient’s outcome, allow healthcare providers to make timely interventions, and plan the course of treatment. This paper presents a mapping of the TAT of X-ray and USG procedures. METHOD: The study used a descriptive research design. It was carried out in one of the teaching hospitals of Gujarat. 110 procedures were taken for the study using the convenient non-random sampling method. Descriptive statistics and a one-sample t-test were applied to fulfil the objective of the study. RESULT: The mean scores of the X-ray procedures and USG procedures were 40.6 and 83.56 respectively. The applied test value was 60. Both methods had a <0.05 significance level. It shows the association between the desired time and the observed time taken for the X-ray and USG procedures. CONCLUSION: As the study mapped the TAT of diagnostic procedures, USG procedures need more attention to identify the waste compared to X-ray procedures from lean management perspective to improve patient satisfaction and return of beneficiaries to the care ratio.